Drug–drug interaction and initial dosage optimization of aripiprazole in patients with schizophrenia based on population pharmacokinetics - Zhang, Cun; Jiang, Lei; Hu, Ke; Zhang, Yi-Jia; Han, Jing; Chen, Jin; Bulubu,; Dong, Boling; Shi, Hao-Zhe; He, Su-Mei; Yu, Ting-Ting; Chen, Xiao; et al. (Frontiers in Psychiatry, 2024)
Background The present study aimed to investigate the drug–drug interaction and initial dosage optimization of aripiprazole in patients with schizophrenia based on population pharmacokinetics. Research design and methods A total of 119 patients with schizophrenia treated with aripiprazole were included to build an aripiprazole population pharmacokinetic model using nonlinear mixed effects. Results The weight and concomitant medication of fluoxetine influenced aripiprazole clearance. Under the same weight, the aripiprazole clearance rates were 0.714:1 in patients with or without fluoxetine, respectively. In addition, without fluoxetine, for the once-daily aripiprazole regimen, dosages of 0.3 and 0.2 mg kg−1 day−1 were recommended for patients with schizophrenia weighing 40–95 and 95–120 kg, respectively, while for the twice-daily aripiprazole regimen, 0.3 mg kg−1 day−1 was recommended for those weighing 40–120 kg. With fluoxetine, for the once-daily aripiprazole regimen, a dosage of 0.2 mg kg−1 day−1 was recommended for patients with schizophrenia weighing 40–120 kg, while for the twice-daily aripiprazole regimen, 0.3 and 0.2 mg kg−1 day−1 were recommended for those weighing 40–60 and 60–120 kg, respectively. Conclusion This is the first investigation of the effects of fluoxetine on aripiprazole via drug–drug interaction. The optimal aripiprazole initial dosage is recommended in patients with schizophrenia.